STUDY OF PROPERTIES OF DIFFUSION-HARDENING COMPOSITE SOLDER GaSn — CuSn — Mo - V.М. Skachkov; L.A. Pasechnik; S.P. Yatsenko (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2020)
The article discusses the possibility of regulating the properties of a diffusion-hardening solder based on a low-melting gallium-tin alloy and a solid component consisting of a copper-tin alloy powder by introducing an inert metal molybdenum powder and heat treatment. The microhardness and thermal stability of composite diffusion-hardening solders were evaluated. It is shown that repeated heat treatment at high temperatures contributes to the transition of the solder to an equilibrium state, with a sharp increase in hardness, almost by an order of magnitude. It is confirmed that inert fillers reduce the mechanical strength relative to the initial diffusion-hardening solder, even those that are well wetted with gallium, but there is a certain range containing a certain amount of the inert component, for molybdenum powder it is 15%, at which the microhardness of the composite solder reaches the maximum.